Acute metabolic changes with thigh-positioned wearable resistances during submaximal running in endurance-trained runners - Field, A. P.; Gill, N.; Macadam, P.; Plews, D. (Sports, 2019)
The aim of this study was to determine the acute metabolic effects of different magnitudes of wearable resistance (WR) attached to the thigh during submaximal running. Twenty endurance-trained runners (40.8 ± 8.2 years, 1.77 ± 0.7 m, 75.4 ± 9.2 kg) completed six submaximal eight-minute running trials unloaded and with WRs of 1%, 2%, 3%, 4% and 5% body mass (BM), in a random order. The use of a WR resulted in a 1.6 ± 0.6% increase in oxygen consumption (VO2) for every 1% BM of additional load. Inferential based analysis found that the loading of =3% BM was needed to elicit any substantial responses in VO2, with an increase that was likely to be moderate in scale (effect size (ES) ± 90% confidential interval (CI): 0.24 ± 0.07). Using heart rate data, a training load score was extrapolated to quantify the amount of internal stress. For every 1% BM of WR, there is an extra 0.17 ± 0.06 estimated increase in training load. A WR =3% of BM was needed to elicit substantial responses in lactate production, with an increase which was very likely to be large in scale (ES ± 90% CI: 0.41 ± 0.18). A thigh-positioned WR provides a running-specific overload with loads =3% BM, resulting in substantial changes in metabolic responses.